Evaluation of The Implementation of The Credit Sales Accounting Information System - Cahyani, Dwi Indri; Hazmi, Yusri; Zuhra, Nazwa Khairun; Wildani, Rifka Ridhatul (West Science Social and Humanities Studies, 2024)
An accounting information system (AIS) consists of a framework that coordinates resources such as data, materials, equipment, suppliers, staff, and money so that economic data can be converted into financial information. In a credit sales system, an agreement is made with the hope of getting paid at a later date within a certain period of time. Investigation methodology the researcher applied a type/methodology of research known as Library Research in this investigation. Researching and asking questions in the library can be used for more than just obtaining research data. This means that library studies can only use library collection materials and do not need to go into the field. However, experts say that literature study is a way of obtaining information by reading books, articles, notes and various reports related to the problem being faced.